The size of topographic depressions in a Sahelian savanna is a driver of woody vegetation diversity. (March 2023) - Dendoncker, Morgane; Vincke, Caroline; Bazan, Samantha; Madingou, Mady Parfait Noé; Taugourdeau, Simon
Abstract: In drylands, water availability is the main limiting factor for plant growth. Topographic depressions in the Sahel that reveal a more favorable water balance display greater tree diversity compared to their surroundings. However, the environmental factors that drive differences in botanical composition between depressions remain unknown. Here, we investigated the depression features, and the landscape and connectivity metrics responsible for woody vegetation composition in a savanna of Senegal. We mapped depressions in a 700 km 2 area and inventoried woody vegetation in 61 depressions varying in area. Simple linear models were applied between (i) indicators of richness and botanical composition and (ii) depression attributes, landscape and connectivity metrics. We found that the area of a depression increased species richness. The number of vegetation strata and the presence of a temporary pond also positively influenced species richness. Yet, while large depressions always had high richness, some small depressions did too. We were not able to identify additional factors to explain this diversity between small depressions. In the context of decreasing richness and composition shift observed in the Sahel over recent decades, depressions, as biodiversity hotspots, are key elements in ecosystem functioning. Further studies are needed to understand other potential drivers of species diversity, such as soil water availability. Highlights: Species richness increases with depression area. Some small depressions have a similar species richness than the largest. Landscape and connectivity metrics weakly influence species diversity. Rare and depression-specific species present higher water requirements. Difference in water availability among depressions should be further investigated.